Incidence of a Capital Income Tax in a Growing Two-Class Economy - Gupta, Kanhaya L. (Review of Economic Studies, 1976)
Journal Article Incidence of a Capital Income Tax in a Growing Two-Class Economy Get access Kanhaya L. Gupta Kanhaya L. Gupta University of Alberta Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 43, Issue 3, October 1976, Pages 561–562, https://doi.org/10.2307/2297238 Published: 01 October 1976 Article history Received: 01 April 1975 Accepted: 01 February 1976 Published: 01 October 1976